2015
DOI: 10.4103/2152-7806.157620
|View full text |Cite
|
Sign up to set email alerts
|

External ventricular drains: Management and complications

Abstract: Background:Insertion of an External Ventricular Drain (EVD) is arguably one of the most common and important lifesaving procedures in neurologic intensive care unit. Various forms of acute brain injury benefit from the continuous intracranial pressure (ICP) monitoring and cerebrospinal fluid (CSF) diversion provided by an EVD. After insertion, EVD monitoring, maintenance and troubleshooting essentially become a nursing responsibility.Methods:Articles pertaining to EVD placement, management, and complications w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
108
0
10

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(120 citation statements)
references
References 12 publications
2
108
0
10
Order By: Relevance
“…Measurement of intracranial pressure (ICP) is used to guide targeted therapy of acute brain injury during a patient's stay in a neurological intensive care unit (NICU) [1][2][3][4][5][6]. External ventricular drain (EVD) remains the gold standard for both monitoring ICP and diverting cerebrospinal fluid (CSF) from the ventricles in clinical situations requiring the management of acute hydrocephalus or temporary CSF drainage [7][8][9]. Several studies have critically examined the effect of ventriculostomy drainage on elevated ICP [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurement of intracranial pressure (ICP) is used to guide targeted therapy of acute brain injury during a patient's stay in a neurological intensive care unit (NICU) [1][2][3][4][5][6]. External ventricular drain (EVD) remains the gold standard for both monitoring ICP and diverting cerebrospinal fluid (CSF) from the ventricles in clinical situations requiring the management of acute hydrocephalus or temporary CSF drainage [7][8][9]. Several studies have critically examined the effect of ventriculostomy drainage on elevated ICP [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proved that CSF drainage significantly reduced ICP and increased cerebral perfusion pressure (CPP) in traumatic brain injury (TBI) patients [10,14,15]. However, how cerebral vessels respond to acute CSF drainage still remains unknown, partly due to the inability of conventional EVD to simultaneously detect ICP waveforms during CSF drainage [7,16], and partly due to the fact that we lack an efficient tool to evaluate cerebral vascular changes continuously. To tackle the first problem, a novel Integra ® Camino ® FLEX Ventricular Catheter (Integra Lifesciences, County Offaly, Ireland) has been introduced into the market recently [17].…”
Section: Introductionmentioning
confidence: 99%
“…The technique most commonly used in clinical practice to monitor ICP involves external ventricular drain (EVD) and intraparenchymal pressure monitor, while the latter only allows ICP monitoring without a combined therapeutic option of cerebrospinal fluid (CSF) drainage [13]. EVD has become a gold standard in a neurological intensive care unit (NICU) for both monitoring ICP and diverting CSF from the ventricles to reduce ICP [14][15][16]. EVD insertion is proved to be valuable, indeed often lifesaving, in intraventricular hemorrhage (IVH), SAH, TBI, and bacterial meningitis [14,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…EVD has become a gold standard in a neurological intensive care unit (NICU) for both monitoring ICP and diverting CSF from the ventricles to reduce ICP [14][15][16]. EVD insertion is proved to be valuable, indeed often lifesaving, in intraventricular hemorrhage (IVH), SAH, TBI, and bacterial meningitis [14,17,18]. However, the conventional EVD system, with one side inserted to ventricle and the other side connected to a collection reservoir to allow for drainage of CSF or to a pressure transduce [19], is not able to simultaneously record ICP pulse waveforms while it is open to drain CSF [14,20].…”
Section: Introductionmentioning
confidence: 99%
“…Infection is the most important of these complications. Ventriculostomy connected infection rate is reported 0% -22% [1] [2]. After the ventriculostomy, so many studies were made for the cause of infection but a common cause has not been found [3]- [8].…”
Section: Introductionmentioning
confidence: 99%